2004
DOI: 10.1103/physrevb.70.195428
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced transmission versus localization of a light pulse by a subwavelength metal slit

Abstract: The existence of resonant enhanced transmission and collimation of light waves by subwavelength slits in metal films [for example, see T.W. Ebbesen et al., Nature (London) 391, 667 (1998) and H.J. Lezec et al., Science, 297, 820 (2002)] leads to the basic question: Can a light be enhanced and simultaneously localized in space and time by a subwavelength slit? To address this question, the spatial distribution of the energy flux of an ultrashort (femtosecond) wave-packet diffracted by a subwavelength (nanometer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
32
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 37 publications
(164 reference statements)
3
32
0
Order By: Relevance
“…17 The surface plasmons and Rayleigh anomalies were involved in explanation of reflective properties of such a kind of gratings. 18 The studies 13,14,15,19 have pointed out that the origin of anomalous scattering of light by a grating of slits (holes) can be better understood by clarifying the transmission and reflection properties of a single subwavelength slit. Along this direction, it was already demonstrated that the intensity of TM-polarized light resonantly transmitted through a single slit can be 10-10 3 times higher than the incident wave 1,2, 3,15 and that the transmission coefficient versus wavelength possesses a Fabry-Perot-like behavior 13,14,15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 The surface plasmons and Rayleigh anomalies were involved in explanation of reflective properties of such a kind of gratings. 18 The studies 13,14,15,19 have pointed out that the origin of anomalous scattering of light by a grating of slits (holes) can be better understood by clarifying the transmission and reflection properties of a single subwavelength slit. Along this direction, it was already demonstrated that the intensity of TM-polarized light resonantly transmitted through a single slit can be 10-10 3 times higher than the incident wave 1,2, 3,15 and that the transmission coefficient versus wavelength possesses a Fabry-Perot-like behavior 13,14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…To com-pare properties of the light reflection with the extraordinary transmission 13,14,15 , we consider the scattering of TM-polarized light by a slit in a thick metallic film of perfect conductivity. From the latter metal property it follows that surface plasmons do not exist in the film.…”
Section: Introductionmentioning
confidence: 99%
“…To address such systems and incorporate the issue of boundary conditions we employ an integral equation formulation [4], [5], [6] describing electromagnetic wave transmission through a nano-hole in a thin plasmonic layer in terms of the dyadic Green's function for the associated vector Helmholtz problem [7], [8], [9], [10]. Interesting electromagnetic phenomena, including enhanced transmission through a nano-hole in an opaque screen, have been discussed in the literature mostly for a metallic thick screen [11], [12], [13], [14]. The aim of the present work is to study electromagnetic wave field transmission and reflection at a thin semiconductor screen including the role of the embedded 2D plas-monic layer, and transmission directly through it as well as through the aperture, thereby improving our understanding of subwavelength electromagnetic phenomenology.…”
Section: Introductionmentioning
confidence: 99%
“…The energy can be enhanced or completely destroyed if the amount of energy spent on the phase modification is smaller than the energy of the Fourier components. The interference phenomenon could be relevant to the variation of the momentum of light in a material medium [38] and the energy variation in an ultra-short light pulse scattering by subwavelength apertures [39]. Taking into account the cross correlation energy could be important also for understanding the enhancement and suppression of energy in other optical processes (for example, see the studies [37,40,41,42] and references therein).…”
mentioning
confidence: 99%
“…The Hamiltonian describing the interference-induced enhancement of the intensity and energy of a multimode quantum optical field is derived. Such a field can be produced, for instance, by a subwavelength array of coherent light sources.PACS numbers: 03.70.+k, 03.75.-b, 03.50.-z Since the demonstration of enhanced transmission of light through a subwavelength metal apertures in the study [1], the phenomenon attracts increasing interest of researchers working in the field of nanooptics and nanophotonics [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27]. It is generally accepted [25] that the excitation and interference of plasmon-polaritons play a key role in the process of enhancement in the most of experiments (see, the recent reviews [26,27]).…”
mentioning
confidence: 99%